Cultural Influence on ESL Students’ Writing - Zhu, Pinfan (International Journal of Linguistics, Literature and Translation, 2022)
Culture and language are closely related. Language is the carrier of culture. The words we write and the ways we communicate often mirror our cultural values, assumptions, beliefs, conventions, and perceptions. So, these elements form the code system by which we encode and decode messages that communicate our ideas. However, when people use their code system to communicate with people from different cultural backgrounds with a different code system, problems are likely to occur. This essay aims at exploring the potential and possible problems that may occur in the use of words and ways of communication when ESL students write in English. It takes ESL learners of Chinese as an example to illustrate the problems. The method is a corpus-based study that focuses on language problems resulting from weak cultural awareness. Major findings include errors in aspects of diction, sentence patterns and discourse patterns, using Chinese students’ writings as examples. The significance of the research lies in that it will enable ESL learners to be on the alert against the cultural influence on their writing in English and quickly realize these different ways so that they can write idiomatic English, not only grammatically correct English. It will also help ESL instructors quickly identify the problematic areas they need to work more with their students. In this sense, the article contributes to both ESL teaching and learning.